Stable intrachain and interchain complexes of neurofilament peptides: a putative link between Al3+ and Alzheimer disease. - Hollósi, M (1994)
The etiologic role of Al3+ in Alzheimer disease has been controversial. Circular dichroism (CD) spectroscopic studies on two synthetic fragments of human neurofilament protein mid-sized subunit (NF-M), NF-M13 (KSPVPKSPVEEKG) and NF-M17 (EEKGKSPVPKSPVEEKG), and their alanine-substituted and/or serine-phosphorylated derivatives were carried out in an attempt to find a molecular mechanism for the effect of Al3+ to induce aggregation of neuronal proteins or their catabolic fragments. Al3+ and Ca2+ ions were found to induce beta-pleated sheet formation in the phosphorylated fragments. The cation sensitivity depended on the length and charge distribution of the sequence and site of phosphorylation. Al3+-induced conformational changes were irreversible to citric acid chelation, whereas Ca(2+)-induced conformational changes were reversible with citric acid. Studies of the alanine derivatives demonstrated which residues affected Al3+ or Ca2+ binding. Peptides containing at least one free (nonphosphorylated) serine residue were shown to form an intramolecular Al3+ complex, rather than an intermolecular one. In the intramolecular (intrachain) complex, the ligand function of the deprotonated serine hydroxyl was delineated [(Al.pepH-1)-type complex]. Ca2+ ions did not show a tendency for intramolecular complexing. The potential role of Al3+ in Alzheimer disease tangle and plaque formation is strongly suggested.